Experimental implant evaluated in grazing yearling steers - S. Laudert; C. Sauerwein (Kansas Agricultural Experiment Station Research Reports, 1986)
An experimental implant containing Beta-estradiol increased (P<.05) daily gain of grazing yearling steers by 15.5% compared to controls. Compudose implants increased (P<.01) daily gain by 13.5%. There was no gain difference between the experimental implant and Compudose.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Yearling steers; Compudose; Implants